Planned Change in the Evolution of Cataract Surgery - Taylor, Teresa; Tremblay, Theresa (Operating Room Nurses Association of Canada Journal, 1998)
The subject of this paper is a description of how perioperative nurses and other health care professionals worked together to meet the demands of change. New technologies and new techniques in cataract surgery with lens replacement has decreased dramatically the amount of operating room (OR) time required. With the reduction in OR time, the process of moving cataract patients through the perioperative experience became chaotic. Change was necessary. Planned change and teamwork made the change process less chaotic and more rewarding.